2013
DOI: 10.1073/pnas.1303551110
|View full text |Cite
|
Sign up to set email alerts
|

Cone photoreceptor types in zebrafish are generated by symmetric terminal divisions of dedicated precursors

Abstract: Proper functioning of sensory systems requires the generation of appropriate numbers and proportions of neuronal subtypes that encode distinct information. Perception of color relies on signals from multiple cone photoreceptor types. In cone-dominated retinas, each cone expresses a single opsin type with peak sensitivity to UV, long (L) (red), medium (M) (green), or short (S) (blue) wavelengths. The modes of cell division generating distinct cone types are unknown. We report here a mechanism whereby zebrafish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
287
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(318 citation statements)
references
References 50 publications
29
287
1
1
Order By: Relevance
“…The rearrangement of those new cone cells after cellular differentiation is considered to play a crucial role in mosaic pattern formation. This is supported by a cell-trace experiment in which most of the cells are found not to change their subtypes after the * Electronic address: noriaki@riken.jp † Electronic address: thatsuda@riken.jp ‡ Electronic address: mochi@riken.jp § Electronic address: mtach@riken.jp first determination [5]. Theoretically, cell rearrangement models for cone mosaics have been formulated on a two-dimensional square lattice: It was found that different patterns (such as the zebrafish pattern with c2mm symmetry and the medaka pattern with p4mg symmetry) can be generated successfully by stochastic cell movements biased by appropriate cell-cell adhesion force [6][7][8].…”
Section: Introductionsupporting
confidence: 49%
See 1 more Smart Citation
“…The rearrangement of those new cone cells after cellular differentiation is considered to play a crucial role in mosaic pattern formation. This is supported by a cell-trace experiment in which most of the cells are found not to change their subtypes after the * Electronic address: noriaki@riken.jp † Electronic address: thatsuda@riken.jp ‡ Electronic address: mochi@riken.jp § Electronic address: mtach@riken.jp first determination [5]. Theoretically, cell rearrangement models for cone mosaics have been formulated on a two-dimensional square lattice: It was found that different patterns (such as the zebrafish pattern with c2mm symmetry and the medaka pattern with p4mg symmetry) can be generated successfully by stochastic cell movements biased by appropriate cell-cell adhesion force [6][7][8].…”
Section: Introductionsupporting
confidence: 49%
“…The true coefficients are known to be rational numbers, so that the above coefficients must be exact although obtained numerically. We find that |λ 5,6,7,8 | are degenerated up to O(g 3 ), and the O(g 7/2 ) contributions start to break the degeneracy. Also, λ 6,7 acquire nonzero real parts from O(g 7/2 ).…”
Section: Perturbation In λmentioning
confidence: 96%
“…This is because in lineagetracing studies two-cell clones derived from Olig2 + , Neurog2 + and Ascl1 + progenitors sometimes contain two photoreceptors and sometimes a photoreceptor and a non-photoreceptor type (Brzezinski et al, 2011;Hafler et al, 2012). Live imaging experiments in zebrafish show that terminal divisions can generate similar diversity, although there are also lineage-restricted cone and rod progenitors (Godinho et al, 2007;He et al, 2012;Suzuki et al, 2013). These results imply that the specification events that define rod and cone fates are not strictly linked to the status of the cell cycle.…”
Section: Transcriptional Network Regulating Photoreceptor Identitymentioning
confidence: 72%
“…However, this is not always the case; it has been known for many years that teleost fish (e.g. zebrafish and goldfish) possess a progenitor that is restricted to producing only rod photoreceptors, although this has been considered an adaptation to maintain light sensitivity and rod density as the retina grows in postembryonic stages (Raymond and Rivlin, 1987), and more recent studies have provided evidence for horizontal-and cone-restricted progenitors in fish (Godinho et al, 2007;He et al, 2012;Suzuki et al, 2013). Together, these studies suggest that many of the specification events leading to the generation of photoreceptors, and even their specific subtype, can occur in either proliferative progenitor or postmitotic precursor (see Glossary, Box 1) cells.…”
Section: Features Of Retinal and Photoreceptor Developmentmentioning
confidence: 95%
“…Knock-down of specific thyroid-regulating genes as well as treatment with different thyroid disruptors resulted in reduced eye size, malformations of eyes and head, and disruption of retinal pigment cell layers of zebrafish larvae (Heijlen et al, 2014;Reider and Connaughton, 2014). It has been reported that cone photoreceptor development seems to be under direct regulation of thyroid hormones (Raine and Hawryshyn, 2009;Suzuki et al, 2013), and it has been described, that thyroid receptors are expressed in the outer nuclear layer of the retina, which contains the developing photoreceptors (Bertrand et al, 2007). The exact pathways still need further investigation, even though a recent study could show that different genes involved in phototransduction are changed in their expression after knockdown of deiodinase enzymes in zebrafish, which regulate intracellular thyroid hormone levels (Bagci et al, 2015).…”
Section: Introductionmentioning
confidence: 99%